Contribution of clinical breast exam to cancer detection in women participating in a modern screening program. - Menes, Tehillah S.; Coster, Dan; Coster, Daniel; Shenhar-Tsarfaty, Shani (BMC Women's Health, 2021)
Purpose: Despite the controversy surrounding the role of clinical breast exam (CBE) in modern breast cancer screening, it is widely practiced. We examined the contribution of CBE in women undergoing routine screening mammography and in women under the screening age.Methods: A retrospective cohort study including all women participating in a voluntary health screening program between 2007 and 2016. All participants undergo CBE; Screening mammography is done selectively based on age, breast imaging history and insurance coverage. Data collected included demographics, risk factors, previous imaging, and findings on CBE and mammography. Cancer detection rates within 3 months of the visit were calculated separately for women undergoing routine screening mammography, and women under the screening age.Results: There were 14,857 CBE completed in 8378; women; 7% were abnormal. Within 3 months of the visit, 35 breast cancers (2.4 per 1000 visits) were diagnosed. In women within the screening age who completed a mammogram less than one year prior to the visit (N = 1898), 4 cancers (2.1 cancers per 1000 visits) were diagnosed. Only one was diagnosed in a woman with an abnormal CBE, suggesting that the cancer detection rate of CBE in women undergoing regular screening is very low (0.5 per 1000 visits). In women under the screening age (45), 3 cancers (0.4 per 1000 visits) were diagnosed; all were visualized on mammography, one had an abnormal CBE.Conclusions: The contribution of CBE to cancer detection in women undergoing routine screening and in women under the screening age is rare.